Facial dominance overrides gender in children’s stereotypes about intelligence - Ryno Kruger; Stella F. Lourenco (Scientific Reports)
Abstract Stereotypes are not only pervasive, they can also lead to discrimination against negatively-stereotyped groups. A gender-intelligence stereotype holds that men and boys are smarter than women and girls, despite no such evidence. Developmental research suggests that even children endorse this stereotype, and negative perceptions about self-worth in girls may be a consequence. Here we tested whether the stereotype about intelligence may, instead, be rooted in facial dominance, such that faces higher in dominance are considered smarter than faces lower in dominance. Across two studies, we found that 6- to 10-year-olds used facial dominance to make intelligence judgments (Experiment 1), even under divided attention (Experiment 2). Children judged more dominant faces as smarter than less dominant faces, whether the two faces were male or female. They did not, however, judge men as smarter than women when selecting between male and female faces that were matched in dominance. What is more, there was some evidence that children considered dominant female faces to be smarter than less dominant male faces, suggesting that dominance in faces may be prioritized over face gender when intuiting intelligence. These findings contrasted with children’s judgments of niceness where both dominance, and a gender stereotype, were used to infer prosociality. Altogether, our findings provide novel evidence for an association between dominance and intelligence, which appears to predate a gender-intelligence stereotype.